The Potential Role of Adipose-Derived Stem Cells in Regeneration of Peripheral Nerves - Sunil P. Mohan; Sivan P. Priya; Nada Tawfig; Vivek Padmanabhan; Rasha Babiker; Arunkumar Palaniappan; Srinivasan Prabhu; Nallan CSK Chaitanya; Muhammed Mustahsen Rahman; Md Sofiqul Islam (Neurology International)
Peripheral nerve injuries are common complications in surgical and dental practices, often resulting in functional deficiencies and reduced quality of life. Current treatment choices, such as autografts, have limitations, including donor site morbidity and suboptimal outcomes. Adipose-derived stem cells (ADSCs) have shown assuring regenerative potential due to their accessibility, ease of harvesting and propagation, and multipotent properties. This review investigates the therapeutic potential of ADSCs in peripheral nerve regeneration, focusing on their use in bioengineered nerve conduits and supportive microenvironments. The analysis is constructed on published case reports, organized reviews, and clinical trials from Phase I to Phase III that investigate ADSCs in managing nerve injuries, emphasizing both peripheral and orofacial applications. The findings highlight the advantages of ADSCs in promoting nerve regeneration, including their secretion of angiogenic and neurotrophic factors, support for cellular persistence, and supplementing scaffold-based tissue repair. The regenerative capabilities of ADSCs in peripheral nerve injuries offer a novel approach to augmenting nerve repair and functional recovery. The accessibility of adipose tissue and the minimally invasive nature of ADSC harvesting further encourage its prospective application as an autologous cell source in regenerative medicine. Future research is needed to ascertain standardized protocols and optimize clinical outcomes, paving the way for ADSCs to become a mainstay in nerve regeneration.